Dextran/eudragit S-100 based redox sensitive nanoparticles for colorectal cancer therapy. Issue 7 (27th January 2023) - Gupta, Aastha; Dhiman, Ankita; Sood, Ankur; Bharadwaj, Ravi; Silverman, Neal; Agrawal, Garima
Abstract : Synthesis of disulfide chemistry based redox sensitive DEEU NPs without using any additional chemical crosslinker for colorectal cancer. Abstract : Herein, we present disulfide crosslinked dextran/eudragit S-100 nanoparticles (DEEU NPs) (≈55 nm) for colorectal cancer treatment. These redox environment sensitive DEEU NPs are synthesized by simple oxidation of thiolated polymers in air. This approach allows avoiding the use of any additional chemical crosslinker. These DEEU NPs have high encapsulation efficiency for the doxorubicin (DOX) model drug (≈95%). The prepared DEEU NPs are redox sensitive owing to disulfide units and exhibit ≈80% DOX release in the reducing environment of GSH. Additionally, DOX-DEEU NPs display enhanced cytotoxicity for HCT116 cancer cells as compared to free DOX. Annexin V staining results also support the higher anticancer efficiency of DOX-DEEU NPs via induction of apoptosis. In vivo biodistribution results demonstrate that DEEU NPs can remain in the colon region for up to 24 hours. These results indicate that DEEU NPs can act as a promising platform for colorectal cancer treatment.